A systematic review: facial, dental and orthodontic findings and orofacial diagnostics in patients with FASD - Blanck-Lubarsch, Moritz; Dirksen, Dieter; Feldmann, Reinhold; Hohoff, Ariane (Frontiers in Pediatrics, 2023)
Background: The fetal alcohol spectrum disorder is a developmental disorder caused by maternal alcohol consumption. Patients with fetal alcohol syndrome show abnormal orofacial features. This review presents an overview over the facial, oral, dental or orthodontic findings and diagnostic tools concerning these features. Methods: For this systematic review Cochrane, Medline and Embase databases were considered and the review was performed according to the PRISMA checklist. Two independent reviewers evaluated all studies and recorded results in a summary of findings table. Risk of bias was analyzed via Quadas-2 checklist. Results: 61 studies were eligible for inclusion. All included studies were clinical studies. Methods and results of the studies were not comparable, guidelines or methods for the detection of FASD varied across studies. Facial features most often measured or found as distinguishing parameter were: palpebral fissure length, interpupillary or innercanthal distance, philtrum, upper lip, midfacial hypoplasia or head circumference. Conclusions: This review shows that to date a multitude of heterogeneous guidelines exists for the diagnosis of FASD. Uniform, objective diagnostic criteria and parameters for the orofacial region in FASD diagnosis are needed. A bio database with values and parameters for different ethnicities and age groups should be made available for diagnosis.